Konformitas Linguistik Digital dalam Penggunaan Bahasa Tidak Baku pada Kolom Komentar TikTok - Windira Nur Azizah; Yanti Linarsih; Ria Kasanova (Pusat Riset dan Inovasi Nasional, 2026)
The increasing use of non-standard language on social media shows that digital language practices are influenced by linguistic, social, and psychological factors. This study aims to describe forms of non-standard language in TikTok comment sections, examine their relationship with Fear of Missing Out (FOMO) culture, and discuss their implications for digital language literacy. Using a descriptive qualitative approach, the study analyzed 68 TikTok comments containing non-standard language taken from viral content with high user engagement. Data were analyzed through the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing. The findings indicate that slang, word shortening, code-mixing, and acronyms are the dominant forms of non-standard language. These forms function as efficient and expressive communication strategies and reflect users’ adaptation to digital community norms. The study also reveals linguistic conformity related to FOMO culture, as users tend to follow popular language practices to maintain social engagement and online relevance. This study introduces digital linguistic conformity as a framework for understanding language reproduction on social media. The findings emphasize the need to strengthen digital language literacy by promoting awareness of both standard language use and diverse digital language varieties in contemporary online communication and youth interaction.